The Paradigm of Cadets of Motivation and Its Impact on Lecturers’ Performance in Maritime Education - Retno Sawitri Wulandari (Journal of Innovation in Educational and Cultural Research, 2023)
The main objective of this study is to explore the cadets' perception of talent management, work motivation, and its impact on the lecturers' performance at Maritime Private Higher Education institutions in DKI Jakarta. The study's population and sample size consisted of 208 participants. To achieve the objective, this research utilized a descriptive and explanatory survey method, with a saturated sampling technique. The data analysis approach involved frequency distribution, grouping, tabulating, and describing the data gathered in the field. The study's findings indicate that the talent management of lecturers at Maritime Private Higher Education institutions in Jakarta has been relatively effective in maintaining good talent. Moreover, the work motivation of the lecturers was found to be highly driven by the need for achievement. The results further indicate that the lecturers' performance in research is outstanding, particularly in preparing scientific reports. This research is significant as it highlights the importance of talent management and work motivation in enhancing the performance of lecturers at Maritime Private Higher Education institutions. The findings can assist academic administrators and policymakers in developing effective strategies for managing and motivating lecturers to improve their performance in teaching, research, and other related activities.